2008
DOI: 10.1177/0886260508314298
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships of Women's Sexual Assault Disclosure, Social Reactions, and Problem Drinking

Abstract: The goal of this exploratory study was to examine correlates of sexual assault disclosure and social reactions in female victims with and without drinking problems. An ethnically diverse sample of sexual assault survivors was recruited from college, community, and mental health agencies. Ethnic minority women were less likely to disclose assault, and women with a greater number of traumatic life events disclosed assault more often. Although there were no differences in disclosure likelihood by drinking status;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 50 publications
6
93
1
Order By: Relevance
“…In fact, no women in the current study reported an experience of sexual victimization to the police. These rates of disclosure to a formal provider are much lower than those documented in a recent community-based study, wherein 38.4% of women told parents, 44.9% of women told a mental health professional, and less than 30% told other formal providers (Ullman et al, 2008). It is likely that college women who fear that the police will respond in a negative way to disclosure (Fisher et al, 2000) are hesitant to discuss sexual victimization to the police.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, no women in the current study reported an experience of sexual victimization to the police. These rates of disclosure to a formal provider are much lower than those documented in a recent community-based study, wherein 38.4% of women told parents, 44.9% of women told a mental health professional, and less than 30% told other formal providers (Ullman et al, 2008). It is likely that college women who fear that the police will respond in a negative way to disclosure (Fisher et al, 2000) are hesitant to discuss sexual victimization to the police.…”
Section: Discussionmentioning
confidence: 82%
“…Victims of stranger-rape and those who sustained physical injuries reported incidents at a higher rate (Ullman et al, 2008), possibly due to an expectation that their report would be believed and handled appropriately (Follingstad & Rogers, 2013;Wolitzky-Taylor et al, 2011). Threats from the accused, along with a growing realization of the toll it would take to follow through with an investigation, are precursors to victims recanting their accusations (Adefolalu, 2014;Sinozich & Langton).…”
Section: Expectation Of Disbelief When Reportingmentioning
confidence: 99%
“…Unacknowledged victims often do not realize that a crime has been committed (Belknap, 2010;Cleere & Lynn, 2013;Lewis-ArĂ©valo & Seto, 2014); frequently know their attacker (Edwards et al, 2015); and are unlikely to report the event to police or campus authorities (Orchowski & Gidycz, 2012;Ullman et al, 2008). Furthermore, by not disclosing their experience, unacknowledged victims potentially miss out on timely support services to aid their recovery and future wellbeing, such as counseling, information about their rights, and medical care, including the collection of a rape kit (Orchowski & Gidycz, 2012;Sinozich & Langton, 2014;Wolitzky-Taylor et al, 2011).…”
Section: "Unacknowledged Victims"mentioning
confidence: 99%
“…To that end, social support has been associated with SA and SA revictimization 26,27 , as well as with risk for psychopathology post-trauma 28–30 . For instance, poor social support following SA has been associated with increased self-blame 31 , lack of interpersonal assertiveness 32,33 , and use of substances to cope 34 , which may in turn increase the likelihood of experiencing a repeated assault 33,35 . Although associations between correlates of social support (e.g., self-blame, lack of assertiveness) and SA revictimization have been identified (e.g., 31,33,36 ), these studies were cross-sectional and mediation cannot be inferred.…”
mentioning
confidence: 99%